Filosofia e matemática nos conceitos simples de Johann Heinrich Lambert: um estudo sobre a concepção de fenomenologia no Neues Organon - Andrade, Luciano Bitencourt de Freitas (2019)
This work proposes to analyze relations between philosophy, mathematics and simple concepts indicated by Johann Heinrich Lambert (c.1728–1777) in his treatise Neues Organon, oder Gedanken Über die Erforschung und Bezeichnung des Wahren und Dessen Unterscheidung vom Irrthum und Schein. Throughout this treatise Lambert attempts to connect what is demonstrated from reality with the structural order of reason. Lambert‟s project of rationality focuses on the complete geometrization of different knowledges and the importance given to order and measurement as the main research criterion. In this way, Lambert understands that science is characterized by the transcription of the signs of illusion, or the activity of nature, in the signs of truth. Throughout this paper we seek to understand how the simple concepts presented in the Neues Organon serve as the foundation for this transposition